Spiritual therapies in nursing care: an integrative review / Terapias espirituais no cuidado de enfermagem: uma revisão integrativa - Santos, Camila Santana dos; Souza, Rozemere Cardoso de; Silva, Thiago Nogueira; Santos, Vanessa Thamyris Carvalho dos; Santos, Josenaide Engracia dos (Journal of Nursing and Health, 2021)
Objective: analyze the scientific production in Nursing about spiritual therapies. Method: integrative review with 41 articles, selected from the Virtual Health Library, between January 9 and February 3, 2020, with the descriptors “Spiritual Therapies” and “Nursing” and the Preferred Reporting Items for Systematic review and Meta-Analysis Protocols methodology. Data were collected through a synoptic chart and critical analysis. Results: increasing studies were identified, especially in the United States and Brazil and in a hospital context, in addition to identifying modalities of spiritual therapies and their contexts of use, training and essential role to Nursing care are described. Conclusions: spiritual therapies promote promote benefits in comprehensive nursing care, in chronic health conditions, in disaster situations, such as the coronavirus disease 2019 pandemic, in the daily lives of different clinics and in promoting well-being.